Cellular Barriers after Extravasation: Leukocyte Interactions with Polarized Epithelia in the Inflamed Tissue - Natalia Reglero-Real; Diego García-Weber; Jaime Millán (Hindawi Limited, 2016)
During the inflammatory response, immune cells egress from the circulation and follow a chemotactic and haptotactic gradient within the tissue, interacting with matrix components in the stroma and with parenchymal cells, which guide them towards the sites of inflammation. Polarized epithelial cells compartmentalize tissue cavities and are often exposed to inflammatory challenges such as toxics or infections in non-lymphoid tissues. Apicobasal polarity is critical to the specialized functions of these epithelia. Indeed, a common feature of epithelial dysfunction is the loss of polarity. Here we review evidence showing that apicobasal polarity regulates the inflammatory response: various polarized epithelia asymmetrically secrete chemotactic mediators and polarize adhesion receptors that dictate the route of leukocyte migration within the parenchyma. We also discuss recent findings showing that the loss of apicobasal polarity increases leukocyte adhesion to epithelial cells and the consequences that this could have for the inflammatory response towards damaged, infected or transformed epithelial cells.